2021
DOI: 10.1097/prs.0000000000008015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Breast Reconstruction Subtype and Risk of Financial Toxicity: A Single-Institution Pilot Study

Abstract: ore than 300,000 women are diagnosed with breast cancer in the United States each year, making it the malignancy with the highest incidence. 1 According to estimates, breast cancer was to be associated with both the highest annualized cost of care ($20 billion) and rate of increase in annual costs by 2020. 2 This number is expected to rise further, coinciding with an escalation in spending on breast cancer treatment driven by innovations in imaging, testing, pharmacotherapy, and surgical treatment. 2,3 Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…16 Also included was a 27-item composite survey derived from published literature, which assessed patient socioeconomic and financial data and evaluated how patients coped with the costs of cancer care. [7][8][9][17][18][19][20] Baseline demographic, clinicopathologic, and operative characteristics were obtained from our prospectively maintained departmental database. Also, collected was the receipt of preoperative therapy, Zubrod performance status, and clinical stage based on the eighth edition of the American Joint Commission on Cancer staging system.…”
Section: Data Sources and Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Also included was a 27-item composite survey derived from published literature, which assessed patient socioeconomic and financial data and evaluated how patients coped with the costs of cancer care. [7][8][9][17][18][19][20] Baseline demographic, clinicopathologic, and operative characteristics were obtained from our prospectively maintained departmental database. Also, collected was the receipt of preoperative therapy, Zubrod performance status, and clinical stage based on the eighth edition of the American Joint Commission on Cancer staging system.…”
Section: Data Sources and Patient Populationmentioning
confidence: 99%
“…In addition, FT can be affected by a variety of clinicopathologic and treatment-related factors. In breast cancer patients, FT was associated with baseline financial well-being and insurance status, employment stability, disease stage, and surgical approach 6–9 . Further, breast cancer survivors who experience FT often experience a worse quality of life and decrease their spending on leisure activities, such as vacations or movies, as well as basic needs including food and clothing 4,10,11 …”
mentioning
confidence: 99%
“…These results echo findings by Bailey et al that demonstrated no differences in out-of-pocket costs according to breast reconstruction subtype, possibly due to most financial exposure being accepted by the insurer regardless of the reconstructive modality; however, future studies are needed to further examine the potential financial toxicity attributed to staged free-flap procedures. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Given the significant cost associated with the use of ADM, the increased cost burden on patients undergoing breast reconstruction, and the similarity in surgical outcomes, it is important for surgeons to consider cost differences among ADMs when choosing the type of ADM for IBR. 25,[33][34][35][36] It is evident that the difference in product price could significantly affect the overall cost of the procedure. 25 Other studies have shown that AlloDerm has a higher cost than SurgiMend and Dermacell.…”
Section: Ementioning
confidence: 99%